Pengaruh Intensitas Cahaya terhadap Jumlah Klorofil dan Laju Fotosintesis pada Berbagai Usia Bibit Kelapa Sawit (Elaeis Guinensis Jaqc) - Fatmawaty, Andi Apriany; Nurmayulis, Nurmayulis Nurmayulis; Susiyanti, Susiyanti Susiyanti; Sodiq, Abdul Hasyim (Jurnal Agroekoteknologi, 2024)
This research aimed to determine the effects of different light intensities and seedling ages on oil palm (Elaeis guinensis Jacq.) nurseries. This research was an experimental type of research carried out from May to August 2023 at the experimental garden of the Faculty of Agriculture, University of Sultan Ageng Tirtayasa, Serang Regency, Banten Province. This research used a factorial split plot design, which consists of two factors. The first factor was the difference in light intensity, which consists of 3 levels: no shade (N0), 20% net shade (N1), and 40% net shade (N2). The second factor or subplot was the age of oil palm seeds, which consists of 3 levels: 3 months of age (B1), 6 months of age (B2), and 9 months of age (B3). The results of the research showed that there was an interaction between light intensity treatment and seedling age that was significantly different in the 1000 nm wave assimilation parameter. The independent influence of light intensity treatment and seedling age occurred on the total chlorophyll parameter. The independent effect of seedling age treatment occurred on the assimilation and evapotranspiration parameters at 1000 nm waves.